Halal tourism MSMEs development: the effectiveness of human resource quality and social media usage / Reinvia Gusti Ashari, Heni Noviarita and Yulistia Devi - Ashari, Reinvia Gusti; Noviarita, Heni; Devi, Yulistia (Universiti Teknologi Mara Selangor, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role and have a considerable influence in supporting the economy of society and national economic development. However, MSMEs still face challenges in their business processes, such as the low quality of human resources and the high effectiveness of social media usage that is not in line with sales turnover. This research uses a quantitative approach, with primary data collected through the distribution of questionnaires to 32 respondents who are MSMEs owners in the Gang PU Banana Chips Center. Multiple linear regression analysis was conducted using SPSS version 25.0 to analyze the data. The results of the study show that the variables of human resource quality and the effectiveness of social media usage have an impact on the development of MSMEs. Furthermore, in the perspective of Islamic economics, the quality of human resources and the use of social media in the Gang PU Banana Chips Center MSMEs have applied the principles of Islamic economics, but it is not yet considered good. This can be seen from the results or services, as well as the productivity of goods and services that have not fully adhered to the concepts of professionalism (itqan), trustworthiness (amanah), and honesty.